The mediating role of entrepreneurial attitude with entrepreneurial education and self-efficacy on students' entrepreneurial mindset - davoud tahmasebzadeh sheikhlar; mahdiye ruhi; amin parvari (مدیریت و چشم انداز آموزش)
Abstract The aim of this research was to examine the mediating role of entrepreneurial attitude, education, and self-efficacy on students' entrepreneurial mindset. The study employed a descriptive-correlational research design and surveyed 273 students from the Faculty of Economic Sciences at Tabriz University, selected through available random sampling from a population of 997 students. The research utilized questionnaires on entrepreneurship education (Denaniveh et al., 2015), entrepreneurial self-efficacy (Zhao et al., 2005), entrepreneurial attitude (Chen & Linan, 2009), and understanding of entrepreneurial mindset (Arnolf & Matthiessen, 2013). Structural equation modeling using the partial least squares method and SmartPLS3 software was employed to test the hypotheses. Results showed that entrepreneurship education significantly influenced entrepreneurial self-efficacy (69%), entrepreneurial mindset (24%), and self-efficacy to entrepreneurial attitude (58%). Additionally, entrepreneurial self-efficacy mediated the relationship between entrepreneurial attitude and entrepreneurial mindset (37%). However, entrepreneurship education did not have a significant impact on entrepreneurial attitude or entrepreneurial mindset through the mediation of entrepreneurial attitude and self-efficacy. Extended abstract Introduction Entrepreneurship plays a crucial role in stabilizing economic activities and fostering competition in every country (Ratten, 2019; Ilonen et al., 2018). Higher education institutions, particularly those in knowledge-based societies, are vital in promoting entrepreneurship education (Siivonen et al., 2020). Effective entrepreneurship education programs can enhance students' entrepreneurial attitude, mindset (Wardana et al., 2020), skills, and motivation (Oosterbeek et al., 2010), ultimately improving their entrepreneurial mentality (Cui et al., 2021). Entrepreneurial mindset, the core of entrepreneurship, refers to the ability of budding entrepreneurs to successfully develop their ventures (Neck & Corbett, 2018). To strengthen the entrepreneurial mindset, several dimensions, including entrepreneurship education (Lindberg et al., 2017), attitude towards entrepreneurship (Ayalew & Zeleke, 2018), and self-efficacy (Aima et al., 2020), must be considered. Given the lack of research on entrepreneurial attitude and mindset, as well as the recent emphasis on the need for further investigation of entrepreneurial mindset (Cui et al., 2019), this study aimed to explore the mediating role of entrepreneurial attitude, education, and self-efficacy on students' entrepreneurial mentality. Theoretical Framework: Entrepreneurship encompasses the ability to create something from nothing, combining risk-taking, creativity, personal success, and innovation. It also involves planning, transforming raw ideas into economic outcomes (Nasiri et al., 2022). Ajzen (1991) conceptualized attitude as the degree to which an individual has a positive or negative evaluation of a desired behavior. Entrepreneurial attitude refers to a learner's thoughts and feelings about entrepreneurship. Behavioral attitudes can be categorized as affective (whether a person finds the behavior pleasurable or not) and instrumental (the beneficial or harmful behavior) (Amofah & Saladrigues, 2022). Entrepreneurship training can influence individuals' attitudes and behavioral goals towards entrepreneurship, as well as enhance their management skills (Korir & Kisubi, 2021). The purpose of entrepreneurship education is to help individuals develop entrepreneurial ability, a combination of diverse information, attitudes, and skills (Ndofirepi et al., 2020). Entrepreneurial self-efficacy is a crucial factor in the entrepreneurial process, as it requires individuals to accept the uncertainty of the business environment, which necessitates preparation, hard work, and tenacity (Bandura, 2006). Entrepreneurial mindset refers to a holistic perception of generating new ideas, assessing opportunities and risks, or starting and running a business, where a person internally evaluates their perceptions based on holistic rather than functional characteristics (Asenge, 2018). Research findings have shown that entrepreneurship training positively and significantly impacts self-confidence, mindset, and attitude (emotional, cognitive, and behavioral), as well as entrepreneurial intention (Darini et al., 2022). Azizi et al. (2021) concluded that there is a positive and significant relationship between a supportive atmosphere and self-efficacy with attitude towards entrepreneurship. Entrepreneurship education significantly increased students' entrepreneurial inspiration, which, in turn, promoted the formation of students' entrepreneurial mindset (Jiatong et al., 2021). The results also showed that entrepreneurial self-efficacy partially mediates the relationship between entrepreneurship education, entrepreneurial mindset, and creativity on entrepreneurial intention. Methodology: This study used a quantitative research method to gain a detailed understanding of how entrepreneurship education affects entrepreneurial mindset as well as to understand the mediating role of entrepreneurial attitude and entrepreneurial self-efficacy. The statistical population studied was 997 students of the Faculty of Economic Sciences of Tabriz University, and 273 people were selected as the sample size according to the Karjesi and Morgan table using the available random sampling method. The research tool includes a questionnaire on students' understanding of entrepreneurship education with three items from Denanyoh et al (2015); Entrepreneurial self-efficacy questionnaire with three items from Zhao et al (2005); Entrepreneurial attitude with four items from Liñán & Chen (2009) and perception of entrepreneurial mindset with four items from Mathisen & Arnulf (2013). Participants were asked to answer the items using a 5-point Likert scale from 1 indicating "strongly disagree" to 5 indicating "strongly agree". The analysis data of this research is in two parts, descriptive and inferential, using SPSS26 software, and in order to test the hypotheses, structural equation modeling using partial least squares method is used using SmartPLS software. Research findings The results revealed that the average scores for entrepreneurship education, entrepreneurial self-efficacy, entrepreneurial attitude, and entrepreneurial mentality were 9.87, 11.11, 16.72, and 15.86, respectively. The path coefficient for the relationship between entrepreneurship education and entrepreneurial self-efficacy was 0.687, indicating that a one-unit increase in entrepreneurship education leads to a 0.687-unit increase in entrepreneurial self-efficacy. The path coefficient for the relationship between entrepreneurship education and entrepreneurial mindset was 0.236, indicating that a one-unit increase in entrepreneurship education results in a 0.236-unit increase in entrepreneurial mindset. The path coefficient for the relationship between entrepreneurial self-efficacy and entrepreneurial attitude was 0.582, indicating that a one-unit increase in entrepreneurial self-efficacy leads to a 0.582-unit increase in entrepreneurial attitude. The path coefficient for the relationship between entrepreneurial attitude and entrepreneurial mindset was 0.633, indicating that a one-unit increase in entrepreneurial attitude results in a 0.633-unit increase in entrepreneurial mindset. Furthermore, the results demonstrated that entrepreneurial self-efficacy plays a mediating role in the relationship between entrepreneurship education and entrepreneurial mindset, with a mediation effect of 0.368. The research findings support the proposed theoretical framework and highlight the importance of entrepreneurship education, entrepreneurial self-efficacy, and entrepreneurial attitude in fostering an entrepreneurial mindset among students. Conclusion: The results indicated a significant relationship between entrepreneurship education and entrepreneurial self-efficacy. This finding aligns with the research findings of Wardana et al. (2020) and Darini et al. (2022). To explain these results, it can be argued that universities provide knowledge about entrepreneurship that enables students to become proficient and skilled in business (Jena, 2020), as well as enhances their ability to identify new business opportunities or investments. Furthermore, they can think more creatively and commercialize new ideas in the form of product development (Mahendra et al., 2017). However, the findings revealed that entrepreneurship education does not have a significant impact on entrepreneurial attitude. This result contradicts the research findings of Kusumojanto et al. (2021); Newman et al. (2019); Darini et al. (2022); Naderi & Amiri (2019); and Mohseni et al. (2023). Additionally, the results demonstrated a significant relationship between entrepreneurship education and entrepreneurial mindset. This finding is consistent with the research results of Jiatong et al. (2021); Cui et al. (2021); Wardana et al. (2020); Handayati et al. (2020); Nowiński et al. (2019); Saptono et al. (2020); and Darini et al. (2022). The role of entrepreneurial self-efficacy in entrepreneurial attitude was also significant. This result aligns with the research findings of Azizi et al. (2021) and Bandura (2012). Bandura (2012) argued that self-efficacy is a fundamental factor that influences behavior through processes, goal setting, outcome expectations, and challenges in situations. The role of entrepreneurial attitude in entrepreneurial mindset was significant. The result of the present research aligns with the findings of Darini et al. (2022); Kawulur et al. (2019); and Cui et al. (2021). Contrary to the findings of Wardana et al. (2020), entrepreneurial self-efficacy did not have a significant impact on entrepreneurial mindset. This result contradicts the findings of Kawulur et al. (2019); McMullen & Kier (2016); and Bandura (2012). The role of entrepreneurship education in entrepreneurial mindset, both with the mediation of entrepreneurial attitude and entrepreneurial self-efficacy, was not significant. These results contradict the findings of Wardana et al. (2020) and Kawulur et al. (2019). Based on the obtained results, the following suggestions can be made: Change educational approaches to focus on increasing self-efficacy in entrepreneurship. Design entrepreneurship education programs that not only provide technical skills but also help students gain confidence and self-belief. Introduce successful entrepreneurs to students through group meetings, entrepreneurial reports, and project collaborations with the entrepreneurial environment. Utilize new technologies, such as virtual education, virtual reality, and social platforms, to enhance the speed and quality of entrepreneurship education. Encourage students to engage in entrepreneurial activities and share their experiences through these platforms. Foster collaboration between universities and educational institutions with successful entrepreneurs. This can be achieved through specialized meetings, entrepreneurial reports, and project collaborations between students and the entrepreneurial environment. Promote a culture that values entrepreneurship as a solution for success and economic growth at the university and society level. This can be done through competitions, rewards, and financial incentives, which can encourage students to engage in entrepreneurial activities.